Birinci Dünya Savaşı ve Uluslararası İlişkilerde İdealizmin Yükselişi - Bilal Karabulut (Gazi Akademik Bakış)
Idealism is one of the most fundamental and basic approaches in international relations. This theory, which tracesits roots back to ancient times, gain edits main importance immediately following World War I. Although Idealism, which has been affiliated with the Wilson Principles and League of Nations, lost its importance in a very shortspace of time and remains in the shadow of Realism, it still has an effect on international relations. The theory has in particular played an important role in the emergence of international relations as an independent discipline. This paper will study the post World War I period, known as a golden era for Idealism, and how the theory has been shaped in this period.